Analysing small scale distribution generation PV and wind system in islanded mode - Jama, Amar Abdi (2021)
A large portion of the world's population still lives in villages with limited available grid-based electrification facilities; energy is an important source of social and economic development. Small scale distribution generation PV and Wind system is considered one of the most prominent sources of energy for sustainable development. A distributed energy system is a technology of interest due to its capability to produce clean, eco-friendly, and small-scale users and rural areas where grid power availability is insufficient. This project focuses on sizing and simulate of small-scale distributed generation systems with PV and wind is analysed using MATLAB SIMULINK. The performance of the PV array is analysed in terms of the MPPT efficiency, and MPPT successfully tracks the array rated power to be 298 W, where the efficiency of the algorithm is 99%. The results indicate that the proposed solar system can be suitable for small scale island when compared with the wind.